Drug‐grafted DNA as a novel chemogene for targeted combinatorial cancer therapy. Issue 2 (22nd March 2022) - Liu, Yuhe; Zhang, Jiao; Guo, Yuanyuan; Wang, Ping; Su, Yue; Jin, Xin; Zhu, Xinyuan; Zhang, Chuan
Abstract: Combinatorial therapy based on chemotherapeutic drugs and gene agents to achieve synergistic antitumor effects has emerged as a new direction for cancer treatment. However, simple and efficient co‐delivery of those two drug categories remains a key challenge in this hot area owing to their substantially different pharmacodynamics, impeding the translational potentials of combinatorial approaches. To address this issue, herein we propose a simple strategy to site‐specifically graft camptothecins (CPTs, a representative chemodrug) onto a DNA with dual functional segments, including an AS1411 aptamer sequence to target the cancer cell and a BCL‐2 antisense sequence to down‐regulate the anti‐apoptotic gene. The obtained DNA‐drug conjugate possesses precise chemical composition, controllable drug loading ratio, and responsive disulfide linkage, which can serve as a novel type of chemogene for combinatorial cancer therapy. In both in vitro and in vivo evaluations, our CPT‐bearing chemogene exhibit the targeted co‐delivery of chemo and gene agents to tumor site, efficient BCL‐2 gene knockdown, and strong induced apoptosis of cancer cells, together leading into an enhanced antitumor efficacy. With simple and precise structure as well as facile synthetic procedure, the new chemogene may turn into a promising drug formulation for combinatorial antitumor treatment. Abstract : A new type of targeted chemogene is constructed through site‐specific grafting camptothecins onto a phosphor othioate DNA containing antisense and aptamer segments. With simple and precise structure, the targeted chemogene shows hallmark properties in both in vitro and in vivo evaluations, including active targeting capability, vigorous gene regulation pitency, and prominent antiumor effect, providing new potentials for a better cancer therapy.